2020
DOI: 10.1101/2020.10.21.20216754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Depressive Disorders and Associated Demographic Factors Among Refugees Amidst COVID-19 in Nakivale Refugee Camp in Southwestern Uganda

Abstract: Introduction: The COVID-19 pandemic and health measures to prevent it have unprecedented effects on the mental health of the refugees. However, the situation of refugees in developing countries is unclear. Thus, this study estimated the prevalence of and associated demographic factors during COVID-19 pandemic. The methodology employed a cross-sectional survey carried out in June 2020 in which 146 adult refugees from Nakivale settlement camp were randomly selected to fill out a questionnaires-demographics and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…The pooled mean age of the participants was 27.19 years (95% CI: 24.31–30.09 years; I 2 = 85.38, p <0.001). A total of eight studies were conducted during the COVID-19 pandemic [ 6 , 14 , 16 , 33 , 53 , 168 171 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pooled mean age of the participants was 27.19 years (95% CI: 24.31–30.09 years; I 2 = 85.38, p <0.001). A total of eight studies were conducted during the COVID-19 pandemic [ 6 , 14 , 16 , 33 , 53 , 168 171 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2,538 refugees were assessed for depression in Uganda, and 1,652 screened positive for depression in eight studies. The prevalence of depression ranged between 45.2% [ 168 ] and 96% [ 36 ]. The pooled prevalence of depression was 67.6% (95 CI: 53.7%-81.5%; I 2 = 94.82, p <0.001) ( Fig 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the 2018 joint inter‐agency Multi‐Sector Needs Assessment which was generalizable to refugee populations from 30 settlements in Uganda, one‐in‐five (22%) refugee households have reported that at least one member was in psychological distress (UNHCR, 2020b), thus highlighting the pervasive well‐being and mental health needs among this population. Moreover, further supportive evidence emerged during the COVID‐19 pandemic that nearly half (47%) of 146 refugees iing in Nakivale criteria for having a depressive disorder (Kabunga & Anyayo, 2020). Depression and psychological distress are also positively associated with suicide in refugee settlements (Bwesige & Snider, 2021).…”
Section: Introductionmentioning
confidence: 98%
“…It is important to note that although the prevalence of mental health issues was relatively high in our study (approximately 43% of all participants screened positive for PTSD, 25% for depression and 23% for anxiety), these estimates are comparable or lower than that observed in other studies in similar and nearby regions. [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%